2014
DOI: 10.1186/1476-4598-13-74
|View full text |Cite
|
Sign up to set email alerts
|

Prostate tumor OVerexpressed-1 (PTOV1) down-regulates HES1 and HEY1 notch targets genes and promotes prostate cancer progression

Abstract: BackgroundPTOV1 is an adaptor protein with functions in diverse processes, including gene transcription and protein translation, whose overexpression is associated with a higher proliferation index and tumor grade in prostate cancer (PC) and other neoplasms. Here we report its interaction with the Notch pathway and its involvement in PC progression.MethodsStable PTOV1 knockdown or overexpression were performed by lentiviral transduction. Protein interactions were analyzed by co-immunoprecipitation, pull-down a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 70 publications
(103 reference statements)
6
44
1
Order By: Relevance
“…These molecules can also be regulated by Notch signalling [23,24], suggesting that PLCε may be involved in the Notch signalling pathway. After silencing PLCε expression, we observed a decrease in Notch1 and Hes1 expression levels in both cell lines tested, which suggests that PLCε may be an upstream regulator of factors with a known critical role in prostate cancer progression [25][26][27].…”
Section: Discussionmentioning
confidence: 85%
“…These molecules can also be regulated by Notch signalling [23,24], suggesting that PLCε may be involved in the Notch signalling pathway. After silencing PLCε expression, we observed a decrease in Notch1 and Hes1 expression levels in both cell lines tested, which suggests that PLCε may be an upstream regulator of factors with a known critical role in prostate cancer progression [25][26][27].…”
Section: Discussionmentioning
confidence: 85%
“…Another study showed that Notch signaling inhibited cell invasiveness in prostate cancer; however, this anti-invasive role of Notch was repressed by prostate tumor overexpressed-1 (PTOV1) (Alana et al 2014), an adaptor protein whose expression is significantly increased in prostate cancer (Benedit et al 2001;Santamaria et al 2003). In PTOV1 knockdown prostate epithelial cells, Notch-dependent expression of Hey1 and Hes1 was up-regulated and constitutively active Notch1 receptor attenuated the invasion and anchorage-independent growth of prostate cancer cells (Alana et al 2014).…”
Section: Notch and Cell Migration And Invasion In Prostate Cancermentioning
confidence: 94%
“…In PTOV1 knockdown prostate epithelial cells, Notch-dependent expression of Hey1 and Hes1 was up-regulated and constitutively active Notch1 receptor attenuated the invasion and anchorage-independent growth of prostate cancer cells (Alana et al 2014). …”
Section: Notch and Cell Migration And Invasion In Prostate Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…Inhibition of Notch pathway has been shown to suppress tumorigenesis of prostate cancers [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49]. Moreover, RBPJ acts downstream of the Notch pathway and has been shown to be essential for a functional activated Notch signaling [13,14,16,17,18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%